Mother and I - Pandit, Madhav Pundalik, 1918- (Pondicherry : Dipti Publications, 1984)
Correspondence, speeches, and writings, chiefly with and on Mother, 1878-1973, by a follower of Aurobindo Ghose, 1872-1950.